An assessment instrument of product versus process writing instruction: a rasch measurement analysis - Palpanadan, Sarala @ Thulasi; Abdul Kadir, Zulida; Ahmad, Iqbal; K. Ravana, Venosha (Academic Research Publishing Group, 2019)
Recent researchers continuously stress on the importance of writing instruction in language learning. Therefore, there is an immense need to have an appropriate instrument to measure the writing instruction and the instrument has to be fully tested for validity. Therefore, we developed and validated an instrument using Rasch Measurement Model to assess two prominent approaches (product approach versus process approach) used in writing instruction contemporarily. We tested the instrument by computing its infit, outfit, item reliability, item separation, item difficulty and item discrimination. The results demonstrated that the instrument showed adequate estimates of reliability in assessing both the approaches used by teachers in ESL classrooms. The raw variance result showed that the accuracy of the items of product approach (85.7%) and process approach (63.7%) were excellent and good. The values of item reliability and item separation for product approach were 0.98 and 6.33, while process approach showed the item reliability and separation values of 0.65 and 1.37 respectively. The results showed that product approach is being dominantly practised that did not enhance students’ writing skills in the long run. To address this issue, we propose a new framework for writing instruction as a guide to ESL teachers.